A Reconfigurable Coplanar Waveguide Bowtie Antenna Using an Integrated Ferroelectric Thin-Film Varactor - K. C. Pan; D. Brown; G. Subramanyam; R. Penno; H. Jiang; C. H. Zhang; M. Patterson; D. Kuhl; K. Leedy; C. Cerny (International Journal of Antennas and Propagation)
A novel printed antenna with a frequency reconfigurable feed network is presented. The antenna consists of a bowtie structure patch radiating element in the inner space of an annulus that is on a nongrounded substrate with a ferroelectric (FE) Barium Strontium Titanate (BST) thin film. The bowtie patch is fed by a coplanar waveguide (CPW) transmission line that also includes a CPW-based BST shunt varactor. Reconfiguration of the compact 8 mm × 8 mm system has been demonstrated by shifting the antenna system’s operating frequency 500 MHz in the 7–9 GHz band by applying a DC voltage bias.